2007
DOI: 10.1007/s10517-007-0231-7
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of In Vitro incorporation of 3H-melatonin into organs of the hypothalamic-pituitary-thyroid system in rats

Abstract: Circadian rhythms of the intensity of 3H-melatonin absorption by organs of the hypothalamic-pituitary-thyroid system were studied in young mature male Wistar rats in summer. The hypothalamus, pituitary, and thyroid gland incorporated 3H-melatonin during the day and night hours, but the intensity of its incorporation in the pituitary and thyroid was high during daytime and low at night, while absorption of the hormone by the hypothalamus tended to be higher at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We recorded an analogous but more clearly pronounced pattern of circadian rhythms of binding of 3 Н-melatonin in the hypophysis where the maximum of this process was observed during daytime, while its minimum was observed at night [66]. At the same time, the intensity of binding of 3 Н-melatonin in the hypothalamus at night showed an opposite trend.…”
Section: The Brain Epiphysis and Hhta: Circadian And Seasonal (Circanmentioning
confidence: 64%
See 2 more Smart Citations
“…We recorded an analogous but more clearly pronounced pattern of circadian rhythms of binding of 3 Н-melatonin in the hypophysis where the maximum of this process was observed during daytime, while its minimum was observed at night [66]. At the same time, the intensity of binding of 3 Н-melatonin in the hypothalamus at night showed an opposite trend.…”
Section: The Brain Epiphysis and Hhta: Circadian And Seasonal (Circanmentioning
confidence: 64%
“…We found that the hypothalamus, hypophysis, and thyroid gland are capable of binding 3 Н-melatonin both during day and night; however, the intensity of its incorporation into the hypophysis and thyroid gland is high in the daytime and low at night. At the same time, the uptake of 3 Н-label by the hypothalamus trends toward an increase at night [66].…”
Section: The Brain Epiphysis and Hhta: Circadian And Seasonal (Circanmentioning
confidence: 87%
See 1 more Smart Citation